O estado no processo de acumulação de capital - o papel da empresa estatal no Brasil - Santos Neto, José Luís (1984)
T h e c a p ita I is t mo d e o f p ro d u c t io n is a p ro c e s s vi h ic h involves a contradiction that cannot be resolved. At a certain stage of its development is creates a necessity for the existence of the category States which, as element of this system presents acapitalist character of class. It appear as a fetish and holding power over the society, modert.ing class confl icts and maintaining them inside the limits of the "social order". The spacial development of this mode of production for the peripheric countries, specially after the World War Ilhas implied a relation with and a more direct presence of t h e peripheric State in its national economy. In t h e especific case, of Brazil, it is through the State-owneu enterprises special Iy of the productive sector, that this presence becomes more expl icit; the State presents itself as the "Iocus" of valorizat.ion/reproduction of capital, specially of the hegemonic private capital. It is inside this context that the State-owned enterprises are insert sometimes as public enterprises, while apparatus of State; sometimes as private enterprises, while capitalist companies. However, besides not ln v a l ld a t ln q the capital ist production logic, we find out that such enterprises are one more instrument used in the acumulation of capital. The economic crisisgenerated by the first "energy crisis " has been uS,egul on the one h a'nd , to snow the role played by the State-owned enterprises while they maintained high levels of investment. On the other hand, si n c e 1979, when is was no more possible to postergate and deny the crisis, those enterprises began to generate inflation and public déficit which have now become out of control.